2020
DOI: 10.1128/aem.01565-20
|View full text |Cite
|
Sign up to set email alerts
|

Salt Stress Response of Sulfolobus acidocaldarius Involves Complex Trehalose Metabolism Utilizing a Novel Trehalose-6-Phosphate Synthase (TPS)/Trehalose-6-Phosphate Phosphatase (TPP) Pathway

Abstract: The Crenarchaeon Sulfolobus acidocaldarius has been described to synthesize trehalose via the maltooligosyltrehalose synthase (TreY) and maltooligosyltrehalose trehalohydrolase (TreZ) pathway and the trehalose glycosyltransferring synthase (TreT) pathway has been predicted. Deletion mutant analysis of single and double deletion strains of ΔtreY and ΔtreT in S. acidocaldarius revealed that next to these two pathways a third, novel trehalose biosynthesis pathway is operative in vivo: the trehalose-6-phosphate (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…In order to characterize the iModulons, we first built a scaffold TRN ( Supplementary File 2 ) based on the existing literature for S. acidocaldarius , consisting of 346 gene-regulator interactions for 28 regulators ( Koerdt et al, 2011 ; Reimann et al, 2012 ; Lassak et al, 2013 ; Märtens et al, 2013 ; Orell et al, 2013 ; Ouchi et al, 2013 ; Vassart et al, 2013 ; Anjum et al, 2015 ; Buetti-Dinh et al, 2016 ; Liu et al, 2016 ; Haurat et al, 2017 ; Li et al, 2017 ; Schult et al, 2018 ; Wagner et al, 2018 ; Lemmens et al, 2019 ; Wang et al, 2019 ; Baes et al, 2020 ; Stracke et al, 2020 ; Suzuki et al, 2020 ; van der Kolk et al, 2020 ). To our knowledge, this is the first comprehensive collection of gene-regulator interactions compiled for S. acidocaldarius .…”
Section: Resultsmentioning
confidence: 99%
“…In order to characterize the iModulons, we first built a scaffold TRN ( Supplementary File 2 ) based on the existing literature for S. acidocaldarius , consisting of 346 gene-regulator interactions for 28 regulators ( Koerdt et al, 2011 ; Reimann et al, 2012 ; Lassak et al, 2013 ; Märtens et al, 2013 ; Orell et al, 2013 ; Ouchi et al, 2013 ; Vassart et al, 2013 ; Anjum et al, 2015 ; Buetti-Dinh et al, 2016 ; Liu et al, 2016 ; Haurat et al, 2017 ; Li et al, 2017 ; Schult et al, 2018 ; Wagner et al, 2018 ; Lemmens et al, 2019 ; Wang et al, 2019 ; Baes et al, 2020 ; Stracke et al, 2020 ; Suzuki et al, 2020 ; van der Kolk et al, 2020 ). To our knowledge, this is the first comprehensive collection of gene-regulator interactions compiled for S. acidocaldarius .…”
Section: Resultsmentioning
confidence: 99%
“…The specific trehalose production was increasing in response to increasing dilution rates. This is a further indication for the role of trehalose production as part of a stress response [ 23 ]. Rising dilution rates put the cell under stress due to the growth rate approaching µ max and the organism is gradually approaching its maximal metabolic capacity [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is still evidence that they play an important role in stress resistance. For example, Glyma.09g073600 and Glyma.18g108100 regulate sucrose-related enzymes to increase resistance to low temperature stress [42]; Glyma.04g119700 regulates maltooligosyltrehalose under salt stress [43]; Glyma.12g054200 is considered to be a factor potentially involved in regulating the salt adaptation of α -galactosidase production [44]. In addition, Baud et al [45] and Santaniello et al [46] found that the Arabidopsis thaliana At3G43190 gene homologous to Glyma.09G073600, plays an important role in the regulation of sucrose synthase activity in plant sugar metabolism, whereas Chary et al [47] found that the At1G68020 homolog of Glyma.04G119700 affects Arabidopsis cellular morphology and plant structure via the activity of trehalose -6-phosphate synthase/phosphatase.…”
Section: Discussionmentioning
confidence: 99%